(untitled) (Journal of Hama University, 2024)
This study aimed to evaluate the prevalence of contamination of feed of poultry and ruminants with the Aspergillus flavus and Evaluate the inhibitory effectiveness of aqueous and alcoholic rosemary extract against the Aspergillus flavus isolated from feed. This study was conducted in the period from 16/5/2023 to 20/8/2023 in the modern chemistry laboratory at the College of Veterinary Medicine at the University of Hama. The study samples were collected from poultry and ruminant feed stores in Hama Governorate. The results of this study showed a high level of contamination of poultry and ruminant feeds with the Aspergillus flavus, as the prevalence of the Aspergillus flavus in poultry feeds reached 24% and 56% in ruminant feeds. The results also showed an inhibitory activity for the aqueous and alcoholic rosemary extracts, as the minimum inhibitory concentration value for the aqueous extract reached 18 mg/ml, while the alcoholic extract was more effective than the aqueous extract, as the minimum inhibitory concentration value for the alcoholic extract reached 14 mg/ml. We conclude from this study that there is a high level of contamination with the Aspergillus flavus in animal feed and the presence of inhibitory activity of aqueous and alcoholic rosemary plant extracts against the Aspergillus flavus.